2019
DOI: 10.3389/fnagi.2019.00329
|View full text |Cite
|
Sign up to set email alerts
|

Biological Sex: A Potential Moderator of Physical Activity Efficacy on Brain Health

Abstract: The number of older people worldwide living with cognitive impairment and neurodegenerative diseases is growing at an unprecedented rate. Despite accumulating evidence that engaging in physical activity is a promising primary behavioral strategy to delay or avert the deleterious effects of aging on brain health, a large degree of variation exists in study findings. Thus, before physical activity and exercise can be prescribed as “medicine” for promoting brain health, it is imperative to understand how differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 131 publications
(171 reference statements)
4
37
0
Order By: Relevance
“…Therefore, differences in sex hormones that act as neurosteroids and interact with molecular growth factors, brain structures and cognition in a different manner for women and men could explain part of this variability (Ansdell et al, 2020 ). Besides, this is in accordance with recent bibliography stating sex differences in the association of exercise with brain and cognitive outcomes (Lindwall et al, 2008 ; Varma et al, 2015 , 2016 ; Barha et al, 2019 ; Dimech et al, 2019 ). Another potential explanation could be a dose-effect bias related to the described differences in the amount of physical activity performed by women and men.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, differences in sex hormones that act as neurosteroids and interact with molecular growth factors, brain structures and cognition in a different manner for women and men could explain part of this variability (Ansdell et al, 2020 ). Besides, this is in accordance with recent bibliography stating sex differences in the association of exercise with brain and cognitive outcomes (Lindwall et al, 2008 ; Varma et al, 2015 , 2016 ; Barha et al, 2019 ; Dimech et al, 2019 ). Another potential explanation could be a dose-effect bias related to the described differences in the amount of physical activity performed by women and men.…”
Section: Discussionsupporting
confidence: 91%
“…One of our relevant results is that frequent exercise was related with greater temporal lobe volume in women and men, which is a key structure for memory and it deteriorates with aging. Moreover, consistent with Barha et al ( 2019 ), women that expended more energy in sportive physical activities had greater dorsolateral prefrontal cortex volume, which is involved in supporting executive functions, especially working memory. In other studies greater CRF levels have been linked to greater brain volumes (Raichlen et al, 2019 ; Wittfeld et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Substantial dietary intervention studies and epidemiological surveys have demonstrated that the consumption of a diet rich in fruits and vegetables has health-promoting effects [ 1 , 2 ]. It is estimated that the proportion of people aged 60 and above will increase from 12% in 2015 to 22% in 2050 [ 3 ]. Thus, delaying or preventing the onset of aging-related diseases due to cellular damage and functional decline would greatly improve life quality and expectancy, as well as mitigate the burden on the current healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the above-mentioned goal will require more information and understanding regarding the mechanisms involved in responsiveness to exercise and better information regarding factors that modulate such responsiveness. There is clear evidence that sex can play a role in responsiveness to exercise at the level of the brain, with females responding more than males (reviewed in Barha et al, 2017Barha et al, , 2019Dao et al, 2019). This is an interesting response pattern since most Alzheimer patients are female.…”
mentioning
confidence: 99%